Developing and assessing a cadaveric training model for transanal total mesorectal excision: initial experience in the UK and USA. (May 2017) - Penna, M.; Whiteford, M.; Hompes, R.; Sylla, P.
Abstract: Aim: Transanal total mesorectal excision (taTME) has become one of the most promising technical advancements in the surgical treatment of rectal cancer, with rising numbers of surgeons seeking training. We describe our experience with human cadaveric courses for taTME delivered in two countries. Method: Four fresh human cadaveric workshops conducted in Oxford, UK, in 2015 and two in Chicago, USA, in 2013−2014, trained a total of 52 surgeons. Parameters of operative performance for each delegate were recorded. Previous surgical experience and uptake of taTME in the surgeons' clinical setting were surveyed. Results: Forty‐seven taTME cases were performed on cadaveric models. Participating surgeons had previous experience in laparoscopic TME surgery and transanal approaches but limited taTME exposure. The purse‐string remained occluded throughout in 93% of UK and 60% of US cases. Operative timings for key procedural steps were similar between the two countries with a mean time from start of circumferential dissection to peritoneal entry of 79.5 min (range 25–155). 96% of surgeons dissected transanally to a level S2 or above. The TME specimen quality was complete or near complete in 81%, with improvements noted between the first and second procedure performed. 81% of surgeons surveyed are currently performing taTME in their local hospitals. Conclusion: Fresh‐frozen cadavers provide excellent teaching models for complex pelvic surgery. A structured training curriculum including reading material, dry‐lab purse‐string practice and postcourse mentorship will provide surgeons with a more complete training package and ongoing support, to ultimately ensure the safe introduction of taTME in the clinical setting.